Unmet needs in histological transformation of follicular lymphoma: a clinical and biological review - Alcoceba, Miguel; Alonso-Álvarez, Sara; García-Álvarez, María; Martín, Alejandro; Caballero, M. Dolores (Annals of Lymphoma, 2017)
Histological transformation, with its profound diagnostic and therapeutic implications, is considered to be one of the most unfavorable events in the natural history of follicular lymphoma (FL). No optimal treatment of transformed follicular lymphoma (tFL) has been identified because of its rarity and heterogeneous presentation, and the lack of data from randomized clinical trials. Consequently, its treatment has been based on that used in de novo diffuse large B-cell lymphomas. However, patients with tFL present a different behavior, with a worse clinical course and poor response to treatment, although their prognosis seems to have improved significantly since the introduction of rituximab into therapeutic schemes. There is no consensus definition of tFL, which prevents the genuine identification of transformation when a biopsy is unavailable. There are no biomarkers at diagnosis that accurately identify patients who will transform. A better knowledge of the pathways leading to transformation would clearly help to identify patients at risk of transformation, and to distinguish them from patients who will relapse with FL and from those who will remain disease-free. This would also facilitate the identification of new drug targets, the design of clinical trials and the treatment of transformation when it arises. In the present review we provide a comprehensive overview of the current open questions in the field of transformation of FL. Large-scale international collaborative studies are required to address these gaps in our knowledge.